FIRST REPORT OF POTATO WHITE MOLD CAUSED BY SCLEROTINIA SCLEROTIORUM IN CHINA - Ojaghian, Seyedmohammadreza (Potato Journal, 2019)
Potato J (2018) 45 (2): 159-162 FIRST REPORT OF POTATO WHITE MOLD CAUSED BY SCLEROTINIA SCLEROTIORUM IN CHINA Seyedmohammadreza Ojaghian1,2 ABSTRACT: During plant diseases evaluation of Hangzhou, a city on south east of China, in September 2017, water-soaked lesions were observed in lower parts of potato plants near the soil in a few fields. In addition, mature black sclerotia were found inside dried out beige lesions. A number of sclerotia were sampled from infected fields and transferred to laboratory. After assessment of myceliogenic and carpogenic germination as well as Koch’s Postulates, the pathogen was identified as Sclerotinia sclerotiorum. To our knowledge, this is the first report of S. sclerotiorum on potato in China.